1999
DOI: 10.1191/096120399678840945
|View full text |Cite
|
Sign up to set email alerts
|

The composition of the lupus band test (LBT) on the sun-protected non-lesional (SPNL) skin in patients with cutaneous lupus erythematosus (CLE)

Abstract: The objective of this study was to analyse the different immunoreactants at the dermo-epidermal junction (DEJ) of patients with cutaneous lupus erythematosus (CLE). Sun-protected non lesional (SPNL) skin biopsies from 65 patients with specific cutaneous manifestations of LE and from 18 patients with other dermatologic diseases were tested using the direct immunofluorescence (DIF) technique. Nineteen out of 65 patients with CLE were affected by systemic LE (SLE). We used the conventional chi-squared test to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
1
17
0
6
Order By: Relevance
“…Our previous research showed that the detection rate of immunoreactants in lesional skin varied from 30% to 50% and that IgM was the most frequent immunoreactant [12], which is consistent with other published data [3], [13][15]. We enrolled 64 patients diagnosed with SLE and examined DIF conducted on lesional skin to assess whether the type and number of cutaneous immunoreactants present in the lesional skin correlated with serological disorders and disease severity as measured by the SLEDAI.…”
Section: Introductionsupporting
confidence: 85%
“…Our previous research showed that the detection rate of immunoreactants in lesional skin varied from 30% to 50% and that IgM was the most frequent immunoreactant [12], which is consistent with other published data [3], [13][15]. We enrolled 64 patients diagnosed with SLE and examined DIF conducted on lesional skin to assess whether the type and number of cutaneous immunoreactants present in the lesional skin correlated with serological disorders and disease severity as measured by the SLEDAI.…”
Section: Introductionsupporting
confidence: 85%
“…In SLE, depositions of immune complexes and complement components have been shown to occur even in apparently normal skin areas and have been used as a tool for diagnosing SLE (Lupus Band Test) [18][19][20][21]. Weak and generally discontinuous immune deposits can be found in sunexposed skin regions in up to 20% of healthy young adults [25].…”
Section: Discussionmentioning
confidence: 99%
“…A number of these patients however, develops other SLE symptoms in the months and years following the initial diagnosis and are retrospectively reclassified as LN [14][15][16]. Therefore, they often represent a diagnostic dilemma at disease onset; clinicians need to distinguish between kidney lesions that represent the first [17][18][19][20][21]. On this basis, we hypothesized that skin biopsies may help distinguishing between LN and FHN and conducted a cross-sectional pilot study on 35 patients.…”
Section: Introductionmentioning
confidence: 99%
“…A positive LBT on sun-protected nonlesional skin (if showing the presence of only one immunoreactant at the DEJ) represents a useful and specific criterion for identifying patients with LE. [13] LBT on sun-protected normal skin may be useful in diagnosing SLE in patients with inconclusive clinical and serological profiles and may be also of prognostic significance, particularly if three immunoglobulins are found at the DEJ. LBT is a laboratory procedure and therefore should be used in conjunction with clinical findings and other serological and immunopathological tests to arrive at a final diagnosis.…”
Section: Sensitivity and Specificitymentioning
confidence: 97%